Is capital flow management effective? Evidence based on U.S. monetary policy shocks. (November 2021) - Wang, Jian; Wu, Jason
Highlights: We use U.S. monetary policy shocks as instruments for a recently developed measure of capital flow management. We find U.S. monetary policy shocks lead to adjustments to the capital flow management in emerging markets, which then affect capital flows. In particular, inflow tightening actions increase after dovish U.S. monetary policy shocks and they materially dampen future net portfolio liability inflows. Abstract: It is challenging to empirically test if emerging markets employ countercyclical capital flow management to combat the large flows driven by global factors, and whether such policy is effective in containing capital flows. The first challenge is that a good gauge of the cyclical dynamics of capital flow management measures is hard to obtain. In addition, the causal effects of capital flow management on capital flows are difficult to establish as such policies are usually endogenous responses to capital flows. We address these issues by using U.S. monetary policy shocks as instruments for a recently developed measure of capital flow management that captures both extensive and intensive margins of policy actions. We find that for a panel of 15 emerging market economies, U.S. monetary policy shocks at quarter t − 1 lead to adjustments to the capital flow management in these countries at t, which then affect capital flows at t + 1. In particular, inflow tightening actions increase after dovish U.S. monetary policy shocks and they materially dampen future net portfolio liability inflows.